Added value of anti-SARS-CoV-2 antibody testing in a Flemish nursing home during an acute COVID-19 outbreak in April 2020. Issue 2 (4th March 2022) - Buntinx, Frank; Claes, Peter; Gulikers, Marjo; Verbakel, Jan; Jan, De Lepeleire; Van der Elst, Michaël; Van Elslande, Jan; Van Ranst, Marc; Vermeersch, Pieter
ABSTRACT: Objectives: To examine the added value of anti-SARS-CoV-2 antibody testing in a nursing home during an acute COVID-19 outbreak. RT-PCR is the gold standard, but can be false-negative. Methods: 119 residents and 93 staff members were tested with RT-PCR test and/or a rapid IgM/IgG test. Of these participants, 176 had both tests, 24 only RT-PCR, and 12 only IgM/IgG in the period April 14 to 16 April 2020. Results: 40 (34%) residents and 11 (13%) staff were PCR-positive. Using a rapid IgM/IgG test, 17 (17%) residents and 18 (20%) staff were positive for IgM and/or IgG (IgM/IgG). Thirty-two PCR-positive residents had an IgM/IgG test: 9 (28%), 11 (34%), and 13 (41%) were positive for IgM, IgG, and IgM/IgG. Ten PCR-positive staff had an IgM/IgG test: 3 (30%), 6 (60%), and 6 (60%) were positive for IgM, IgG, and IgM/IgG. Additional IgM/IgG tests were performed in 9 residents 11 to 14 days after the positive RT-PCR test. Of those, 7 (78%) tested positive for IgM/IgG. When retested 3 weeks later, the 2 remaining residents also tested positive. Of the 134 PCR-negative participants who had an IgM/IgG test, 15 were positive for IgM/IgG (8% of the 200 participants tested with RT-PCR). Conclusions: During an acute outbreak in a nursing home, 26% of residents and staff were PCR-positive. An additional 8% was diagnosed using IgM/IgG antibody testing. The use of RT-PCR alone as the sole diagnostic method for surveillance during an acute outbreak is insufficient to grab the full extent of the outbreak.